Analysis of the Influence of Salary and Benefits, Work Environment, and Career Development on Nurses’ Job Satisfaction at Bhakti Asih Hospital, Tangerang City, Banten - Dwaputra, Nandra Djajantya; Tarigan, Samuel (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the influence of salary and benefits, work environment, and career development on nurses’ job satisfaction at Bhakti Asih Hospital, Tangerang. A quantitative approach using a survey method was employed, involving 254 nurse respondents. The results indicate that the work environment and career development have a significant and positive impact on job satisfaction, while salary and benefits show no significant effect. These findings suggest that hospital management should focus on improving the work environment and career development programs to enhance nurses’ satisfaction and retention in a sustainable and targeted manner based on organizational needs.